Penjadwalan Dinas Pegawai Menggunakan Algoritma Evolution Strategies pada PT. Kereta Api Indonesia (KAI) DAOP 7 Stasiun Besar Kediri - Winda Fitri Astiti; Dian Eka Ratnawati; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Scheduling employee service of PT. Kereta Api Indonesia aims to plan the number of employees on duty in turns based on each service time. Employee service scheduling is designed to meet scheduling in accordance with established standard operating procedures. The problem of scheduling the employee service has a very high complexity because in scheduling many factors must be considered such as the hours of work and the number of employees required by the office on a daily basis. The data used in this study is employee data of 14 employees who will be scheduled service. The algorithm used in this research is Algorithm Evolution Strategies. In the process of Evoluiton Strategies Algorithm the representation of chromosomes used is a representation of permutations, with length of gene 98, adjusted for the number of employees and the number of days for scheduling the employee service. The process of reproduction, mutation process using insert mutation. Process valuate the fitness value obtained from the calculation of the number of penalty value of each individual while the selection process used is elitism selection. In this algorithm generate scheduling according to the rules based on the optimal parameter of population size of 80 and many generations of 70 with average fitness value of 0.2. The result of this system is scheduling for a seven-day official schedule that complies with standard operating procedures established.